Taxonomic study of the leafhopper genus Rufitidia (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species - Zou, Hongfen; Lin, Shuanghu; Huang, Min; Zhang, Yalin (Zootaxa, 2022)
The genus Rufitidia Dworakowska is reviewed with two new species from China: R. fissa sp. nov. and R. dissidens sp. nov. Detailed morphological descriptions and illustrations of these two new species and a key to all known species (males) are provided.